2014
DOI: 10.7314/apjcp.2014.15.7.3005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ubiquitin-conjugating Enzyme 2C on Invasion, Proliferation and Cell Cycling of Lung Cancer Cells

Abstract: The aims of this study were to investigate the influence of ubiquitin-conjugating enzyme E2C (UBE2C) on biological behavior of lung cancer cells. Using MTT, flow cytometry and invasion assays, we detected UBE2C expression and evaluated its biological properties in these cells, including effects on proliferation, the cell cycle profile and invasive capability. Compared with control cells, the UBE2C transfected cells demonstrated increased cellular proliferation (p<0.05). UBE2C transfected cells also had a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In addition, the expression of UBE2C was positively correlated with histological grade, tumor size, clinical stage and lymph node metastasis of BRCA. In vitro experiment in previous articles have also proved that UBE2C could enhance the proliferative, viability and invasive capacity through MTT, colony formation assay and invasion assays in lung cancer and prostate cancer [ 31 , 32 ], which increased the reliability of our result that UBE2C exerted an oncogenic influence on breast cancer cells. There was also a difference between UBE2C expression in different molecular subtypes of breast cancer, among which the positive rate of UBE2C expression in HER2-overexpression BRCA was the highest, while the positive expression rate of UBE2C was the lowest in Luminal A BRCA.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, the expression of UBE2C was positively correlated with histological grade, tumor size, clinical stage and lymph node metastasis of BRCA. In vitro experiment in previous articles have also proved that UBE2C could enhance the proliferative, viability and invasive capacity through MTT, colony formation assay and invasion assays in lung cancer and prostate cancer [ 31 , 32 ], which increased the reliability of our result that UBE2C exerted an oncogenic influence on breast cancer cells. There was also a difference between UBE2C expression in different molecular subtypes of breast cancer, among which the positive rate of UBE2C expression in HER2-overexpression BRCA was the highest, while the positive expression rate of UBE2C was the lowest in Luminal A BRCA.…”
Section: Discussionsupporting
confidence: 69%
“…UBE2C is one of the genes used in molecular classification in several types of cancers. Studies revealed that overexpression of UBE2C is related to some kinds of solid tumors, such as stomach cancer (Zhang H. Q. et al, 2018 ), colorectal cancer (Cacciola et al, 2016 ; Zhang Y. et al, 2018 ), esophageal cancer (Matsumoto et al, 2014 ; Li et al, 2018 ), pancreatic cancer (Zhao et al, 2013 ), breast cancer (Mo et al, 2017 ; Qin et al, 2017 ), ovarian cancer (Martínez-Canales et al, 2018 ), hepatocellular cancer (Ieta et al, 2007 ), lung cancer (Tang et al, 2014 ; Zhang et al, 2015 ), prostate cancer (Shuliang et al, 2013 ), and other cancers (Wagner et al, 2004 ; Shen et al, 2013 ; Kraft et al, 2017 ). Therefore, UBE2C has been considered as an important functional gene in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…KIF20A promoted cell proliferation and inhibit apoptosis in LUAD [45]. And UBE2C was found to enhance lung cancer growth [46]. Subsequently, we predicted 30 DElncRNAs and 35 DEmiRNAs, in which 7 DEmiRNAs and 7 DElncRNAs functioned as prognostic biomarkers in LUAD.…”
Section: Discussionmentioning
confidence: 87%
“…KIF20A promoted cell proliferation and inhibit apoptosis in LUAD 45 . And UBE2C was found to enhance lung cancer growth 46 .…”
Section: Discussionmentioning
confidence: 99%